Neurological abnormalities in 97 dogs with detectable pituitary masses. Issue 1 (1st January 2019) - Menchetti, Marika; De Risio, Luisa; Galli, Greta; Bruto Cherubini, Giunio; Corlazzoli, Daniele; Baroni, Massimo; Gandini, Gualtiero
Abstract: Background: Pituitary tumours are common neoplasms of the sellar region in small animals. However, detailed information regarding the spectrum and severity of possible neurological signs are lacking. Objective: To retrospectively describe the neurological abnormalities in a population of dogs with a detectable pituitary mass (DPM) and relate them with the size of the mass and magnetic resonance imaging (MRI) signs of brain compression (BC). Client-owned dogs were included in the study if they had MRI showing a DPM and a detailed neurological examination. The neurological signs were evaluated in relation to the pituitary height/brain ratio (P:B ratio) and the presence/absence of brain compression. Results: Ninety-seven dogs were enrolled. Besides abnormal mentation and behaviour (77%), gait (61%) and cranial nerve abnormalities (44%), other unreported neurological signs observed included postural abnormalities (21%), pain and/or hyperesthesia (25%) and abnormal postural and proprioceptive reactions (49%). The majority of dogs with DPM had signs of BC. The presence of a high pituitary height/brain area and BC represented a risk factor for developing mental status abnormalities. Conclusion: Neurological signs recorded in DPM-affected dogs include not only the typical forebrain signs but also gait disturbances and hyperesthesia. Neurological signs are positively associated with increased P:B ratio and MRI signs of brain compression.